Correlation of molecular and morphological features of appendiceal epithelial neoplasms - Tsai, Jia H; Yang, Ching‐Yao; Yuan, Ray‐Hwang; Jeng, Yung‐Ming (Histopathology, 2019)
Aims The aims of this study were to identify the genetic features of appendiceal epithelial neoplasms and correlate the genetic features with morphology. Methods and results We analysed the genetic features of a series of 47 appendiceal epithelial neoplasms of various morphologies by using targeted next‐generation sequencing of 11 genes commonly mutated in gastrointestinal neoplasms. Seven of nine serrated polyps harboured BRAF mutations, which are rare in other types of appendiceal tumours. Most cases of low‐grade appendiceal mucinous neoplasms (LAMNs) exhibited GNAS and KRAS mutations. LAMNs with a coexisting serrated polyp were all KRAS mutated. Four LAMNs with mutations in the Wnt/β‐catenin pathway, either through inactivating mutations in APC or RNF43 or activating mutations in CTNNB1, had focal proliferation of mucin‐poor low‐grade tumour cells, reminiscent of colorectal adenomas. Mutations in the Wnt/β‐catenin pathway were also identified in high‐grade appendiceal mucinous neoplasms, suggesting that Wnt/β‐catenin pathway activation is the driving force for the progression of LAMN to a higher‐grade lesion. Adenomatous polyps of the appendix frequently had APC, KRAS and TP53 mutations and were morphologically and molecularly similar to adenomatous polyps of the colorectum. Conclusions Our results indicate a close association between morphology and genetic events in appendiceal neoplasms and suggest a phylogenetic relationship between different entities.